Comparison of the transmission of Theileria parva between different instars of Rhipicephalus appendiculatus - Ochanda, H.; Young, A.S.; Wells, C.; Medley, G.F.; Perry, Brian D. (Cambridge University Press, 1996)
The transmission of Theileria parva by nymphal and adult Rhipicephalus appendiculatus was compared by the assessment of salivary gland infections in tick batches fed on the same group of infected cattle at the same time. When larval and nymphal R. appendiculatus Muguga ticks were fed concurrently on cattle undergoing acute infection with T. parva Muguga, the resultant nymphae developed a slightly lower prevalence of infection than did the adult ticks. The abundance of infection was 5-20 times higher in the adult ticks than in the nymphae. When larval and nymphal R. appendiculatus Muguga and R. appendiculatus McIlwaine were fed to repletion on cattle infected with T. parva Boleni, a prasite causing subacute infection, resultant adult tick batches has a relatively high prevalence of infection, but infection was not detected in resultant nymphal batches. When cattle that were carriers of 2 stocks of T. parva, Marikebuni and Kiambu 5, were used as the source of infection, the infections developing in adult R. appendiculatus Muguga ticks were much higher than those developing in nymphae. The structure of salivary glands differed between nymphal ticks, adult males and adult females, and this is considered to be an important factor affecting the infection levels. The morphology of the type III acini, the target acini for sporogony, was similar, but the mean numbers of type III acini were different, with 87 in nymphae, 1346 in males and 1736 in females. This difference was correlated with the different infection levels produced in the various instars and sexes. While the process of sporogony in the different tick instars and sexes was similar, the rate of sporogony was fastest in feeding nymphae, taking on average 2-3 days, compared to 3-4 days in females and an irregular period in the males. These results are discussed in relation to the epidemiology of T. parva.